The light of days [compact disc, unabridged] : the untold story of women resistance fighters in Hitler's ghettos - Batalion, Judith (Harper Audio, 2021)
Brave Jewish women in Poland became resistance fighters, training youth groups to fight the Nazis. "Ghetto girls" paid off -- or seduced and killed -- Gestapo guards, smuggled weapons, bombed German train lines, nursed the sick and taught children in order to help their people.